Occupation-focused interventions for well older people: An exploratory randomized controlled trial. (November 2014) - Zingmark, Magnus; Fisher, Anne G.; Rocklöv, Joacim; Nilsson, Ingeborg
Abstract Objective: The aim of this exploratory randomised controlled trial (RCT) was to evaluate three different occupation-focused interventions for well older people by estimating effect sizes for leisure engagement and ability in activities of daily living (ADL) and thereby identifying the most effective interventions. Methods: One hundred and seventy seven persons, 77–82 years old, living alone and without home help, were randomized to a control group (CG), an individual intervention (IG), an activity group (AG), and a one-meeting discussion group (DG). All interventions focused on occupational engagement and how persons can cope with age-related activity restrictions in order to enhance occupational engagement. Data were collected by blinded research assistants at baseline, three, and 12 months. Ordinal outcome data were converted, using Rasch measurement methods, to linear measures of leisure engagement and ADL ability. Standardized between-group effect sizes, Cohen's d, were calculated. Results: While all groups showed a decline in leisure engagement and ADL over time, the IG and the DG were somewhat effective in minimizing the decline at both three and 12 months. However, the effect sizes were small. Conclusions: The findings indicate that occupation-focused interventions intended to minimize a decline in leisure engagement and ADL were sufficiently promising to warrant their further research.